HUBUNGAN MODUL DEDEKIND DENGAN MODUL PHI MELALUI MODUL INVERTIBEL DAN MODUL PADAT - , AWAN KURNIADI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Let M be a R-module with R is a commutative ring with 1R and let N be a submodule of M. Let S be a multiplicative closed subset R containing no zero divisors of R and T = fs 2 Sjsm = 0 for some m 2 M implies m = 0g. From R and T, a quotient ring of R over T is formed which is denoted as RT . Submodule N of M is said to be invertible if every submodule N have an inverse in M, or for every submodule N in M, there exist an N0 = fx 2 RT jxN Mg such that N0N = M. Furthermore, if every submodules N of M is invertible then M is called Dedekind module. Furthermore from R-moduleM and submodule, a set of all homomorphisms from N to M is formed which is denoted as Hom(N